Exploring and describing the responsibilities and functions of emergency medical communication centers in South Africa: a modified delphi study - Van Schalkwyk, Riekert Dewald (Division of General Surgery, 2025)
Introduction: A significant number of South Africans are reliant on Emergency Medical Services (EMS) for access to Emergency Care, a need compounded by the current quadruple burden of disease. Efficient allocation of EMS resources ensures optimal use in time-critical emergencies. Development and improvement of Emergency Medical Dispatch practices implemented in Emergency Medical Communication Centers (EMCC) have been proposed as a means to improve EMS effectiveness. Establishing priority EMCC functions and responsibilities relevant to South African EMCCs could provide insight into practices requiring further strengthening and development. The aim of this study was to identify and categorise the functions and responsibilities of EMCCs in the South African setting. Methods: A three-round modified E-Delphi was undertaken to establish priority EMCC functions and responsibilities relevant to the South African setting. Fifty-seven statements related to EMCC functions and responsibilities retrieved from the literature review, across six categories, were sent out to 25 EMCC experts from government and private EMSs using LimeSurvey™ software. Results: A total of 68 (88%) out of 77 functions and responsibilities' statements reached consensus (70% agreement) as “essential” to South African EMCCs. Most of the statements related to Systems, Dispatch and Continuous Quality Improvement categories. The remaining 9 (12%) statements did not achieve consensus as essential, desirable or non-applicable, however a clear tendency toward a higher or lower rating of contextual applicability was evident. Conclusion: The majority of EMCC functions and responsibilities described in High-Income Country studies were found to be applicable and were classified by the expert panel as essential for South African EMCC. The methods used as well as the contextualized results could be applied in similar settings to identify developmental priorities. African Relevance Formal EMS systems are in varying stages of development across the African continent. This study sought to establish the important South African relevant Emergency Medical Dispatch elements to address the need for efficient Emergency Medical Services. Although South Africa has had a well-established formal EMS system for the past few decades, the development and functioning of Emergency Medical Call Centres may have been neglected. Understanding and prioritising the functions and responsibilities of such call centres can be extrapolated to other African countries in the early stages of establishing formal EMS systems.